Gas Flow Formation in the Inertial Filtering (IF) Gas Separators Curvilinear Channels (Journal of Engineering, 2014)
This paper deals with an up to date problem for oil and gas industry- separation of the gas -fluid fogs. Here is described the worked out physical model of the gas movement process in the sections of the inertial filtering (IF) gas separators. One can find the mathematical model for research of the fields of velocities and pressures in the inertial curvilinear channel. The main simplifications and assumptions are explained. This mathematical model has been made using mathematical program Maple and it is received the 3-d graphic of the distribution componential speed parts in the channel and also 2-d graphics at the channel sectional view when the flow is flat. The new method for gas - fluid systems separation is suggested.